Case Report: Neurodegenerative Diseases After Severe Acute Respiratory Syndrome Coronavirus 2 Infection, a Report of Three Cases: Creutzfeldt–Jakob Disease, Rapidly Progressive Alzheimer's Disease, and Frontotemporal Dementia - Pimentel, Gabriela Almeida; Guimarães, Thiago Gonçalves; Silva, Guilherme Diogo; Scaff, Milberto (Frontiers in Neurology, 2022)
The relationship between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and neurodegenerative diseases is yet to be fully clarified. Rapid worsening and even new-onset cases of those disorders have been reported in association with coronavirus disease 2019 (COVID-19). We describe three cases of neurodegenerative diseases in patients with SARS-CoV-2: a case of Creutzfeldt–Jakob disease during the COVID-19 acute phase, to our knowledge, is the second one described in the literature; a rapidly progressive Alzheimer's Disease; and a patient with frontotemporal dementia, and a quick decline of both cognitive and behavioral domains. This report suggests an association between SARS-CoV-2 infection and a higher probability of developing or accelerating neurodegenerative chronic neurologic conditions. We reinforce the need for a close cognitive follow-up in the aftermath of Sars-Cov2 infection.